Development of Arabic Educational Animation for Tourism in Arabic Education Study Program at IAIN Manado - Mubarak, Muhammad Husni; Utomo, Nur Fadli (Jurnal Ilmiah Iqra', 2024)
The study aims to develop animated educational media for Arabic for Tourism and to determine its impact on lecture activities in the Arabic Education Study Program. The development of animated education media is necessary to enhance the learning experience and the effectiveness of learning outcomes in the classroom, particularly in the Arabic for Tourism class, which focuses on understanding basic procedures for serving Arabic-speaking tourists and communication processes. It is hoped that the use of video-based media will also increase its utilization as it can be accessed on various devices, anytime and anywhere.The methodology of this study uses a Research and Development (R&D) basis with the ADDIE approach, which includes analysis, design, development, implementation, and evaluation. The study's test variables consist of two test variables: motivation and interest in learning, with a total of 35 respondents.The study results indicate that the Arabic educational animation media for tourism, when reviewed by experts, shows that the content and design are rated very good, with an average score of 80-81%, thus meeting expert criteria. Furthermore, during the evaluation, it shows a fairly good effectiveness regarding the variables of motivation and interest in learning. The learning motivation variable has an average effectiveness of 68.6%, and the interest in learning variable has an average effectiveness of 68.9%, thus being considered quite good in the evaluation results of the Arabic language learning animation media for tourism.Keywords: educational media, Arabic language, tourism